Association between prolonged stress caused by COVID-19 pandemic and earthquakes and quality of life, anxiety, depression, psychoactive substances, and problematic alcohol use in adult Croatian population - Kovačić Petrović, Zrnka; Peraica, Tina; Blažev, Mirta; Kozarić-Kovačić, Dragica (Frontiers in Psychiatry, 2024)
Background The prolonged stress experience caused by the COVID-19 pandemic and two earthquakes led to increased alcohol and psychoactive substance use (PSU) accompanied by a decrease in mental wellbeing and quality of life (QoL) in the Croatian population. Our aim was to determine the relationship between alcohol and PSU and mental health outcomes including anxiety and depression, and QoL. Methods A cross-sectional online survey conducted from September 30 to October 27, 2021, included 1,118 Croatian adults (220 men and 898 women; mean age, 35.1 ± 12.3 years) recruited through non-probabilistic convenience sampling. The survey consisted of a self-reported questionnaire on PSU, the CAGE Alcohol Questionnaire, the Hospital Anxiety Depression Scale, and the World Health Organization Quality of Life (WHOQoL)—BREF. Structural equation modeling was used to evaluate the association between PSU, problematic alcohol use (PAU), mental health outcomes, and QoL. Results The model demonstrated a good fit and indicated that PSU increase, PAU, and anxiety and depression symptoms significantly explained all QoL domains (p < 0.001 for all). Both PSU increase and PAU during prolonged stress were directly associated with decreased QoL. These relationships were also indirectly mediated through increased anxiety and depression symptoms. Conclusion These results showed the need to direct public health interventions and treatment interventions during and after long-term stress (pandemics and earthquakes) to reduce the negative impact on substance use and QoL by reducing depression and anxiety, which ultimately may contribute to better wellbeing and rapid recovery of individuals affected by prolonged stress.